Weaver syndrome and EZH2 mutations: Clarifying the clinical phenotype. Issue 12 (8th November 2013) - Tatton‐Brown, Katrina; Murray, Anne; Hanks, Sandra; Douglas, Jenny; Armstrong, Ruth; Banka, Siddharth; Bird, Lynne M.; Clericuzio, Carol L.; Cormier‐Daire, Valerie; Cushing, Tom; Flinter, Frances; Jacquemont, Marie‐Line; et al.
Abstract : Weaver syndrome, first described in 1974, is characterized by tall stature, a typical facial appearance, and variable intellectual disability. In 2011, mutations in the histone methyltransferase, EZH2, were shown to cause Weaver syndrome. To date, we have identified 48 individuals with EZH2 mutations. The mutations were primarily missense mutations occurring throughout the gene, with some clustering in the SET domain (12/48). Truncating mutations were uncommon (4/48) and only identified in the final exon, after the SET domain. Through analyses of clinical data and facial photographs of EZH2 mutation‐positive individuals, we have shown that the facial features can be subtle and the clinical diagnosis of Weaver syndrome is thus challenging, especially in older individuals. However, tall stature is very common, reported in >90% of affected individuals. Intellectual disability is also common, present in ∼80%, but is highly variable and frequently mild. Additional clinical features which may help in stratifying individuals to EZH2 mutation testing include camptodactyly, soft, doughy skin, umbilical hernia, and a low, hoarse cry. Considerable phenotypic overlap between Sotos and Weaver syndromes is also evident. The identification of an EZH2 mutation can therefore provide an objective means of confirming a subtle presentation of Weaver syndrome and/or distinguishing Weaver and Sotos syndromes. As mutation testing becomes increasingly accessible and larger numbers of EZH2 mutation‐positive individuals are identified, knowledge of the clinical spectrum and prognostic implications of EZH2 mutations should improve. © 2013 Wiley Periodicals, Inc.